A Geological comparison of the Espungabera Formation of central Mozambique and the Straumsnutane Formation of western Dronning Maud Land Antarctica - Roberts, R.J. (James) (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 2015.